Alfa-fetoprotein secreting ovarian sex cord-stromal tumor - Kusum D Jashnani; Chandrashekar V Hegde; Shrutika P Munot (Wolters Kluwer Medknow Publications, 2013)
Ovarian sex cord-stromal tumors are relatively infrequent neoplasms that account for approximately 8% of all primary ovarian tumors. They are a heterogeneous group of neoplasms composed of cells derived from gonadal sex cords (granulosa and Sertoli cells), specialized gonadal stroma (theca and Leydig cells), and fibroblasts. They may show androgenic or estrogenic manifestations. We report such a tumor associated with markedly raised serum alpha-fetoprotein (AFP) levels in a young female presenting with a mass and defeminising symptoms. Serum AFP levels returned to normal on removal of tumor.